(untitled) (The Planet, 2024)
Introduction: Rheumatoid arthritis (RA) is a chronic inflammatory disorder that significantly impacts patients’ quality of life. Conventional daily dosing of Disease-Modifying Antirheumatic Drugs (DMARDs) is the standard treatment approach, but it often leads to side effects and adherence issues. This study explores the efficacy and tolerability of an innovative alternate day DMARD regimen in RA management. Methods and materials: This study was conducted at the Department of Orthopedic Surgery and Traumatology, Khwaja Yunus Ali Medical College Hospital, Sirajganj, Bangladesh from January 2023 to June 2023. This prospective observational study involved 70 RA patients, with 30 in the trial group receiving an alternate day regimen (Methotrexate 2.5 mg on Saturdays, Mondays, and Wednesdays; Folic Acid 5 mg on Sundays, Tuesdays, and Thursdays; Sulfasalazine 500 mg twice on Sundays, Tuesdays, and Thursdays) and 40 in the conventional group receiving Methotrexate 7.5 mg weekly and Sulfasalazine 500 mg twice daily. The primary outcomes measured were improvement in joint pain, swelling, physical function, and the incidence of gastrointestinal complications. Result: The trial group showed a higher improvement in joint pain (80% vs. 70%), joint swelling (70% vs. 60%), and physical function (63.33% vs. 50%) compared to the conventional group. Additionally, the trial group experienced fewer gastrointestinal complications (6.67% vs. 15%). Conclusion: The alternate day dosing regimen of DMARDs demonstrated a potential for greater efficacy and better tolerability in managing RA symptoms compared to the conventional daily regimen. These findings suggest that alternate day dosing could be a viable treatment option for RA, warranting further investigation in larger, long-term studies.